The Rheb-mTORC1 Coordinates Cell Cycle Progression and Endoreplication in Bombyx mori - Zhangchen Tang; Huawei Liu; Qingsong Liu; Xin Tang; Jiahui Xu; Gan Luo; Qingyou Xia; Ping Zhao (Insects)
The mechanistic target of the Rapamycin complex 1 (mTORC1) signaling pathway plays a pivotal role in regulating crucial life processes, including cell growth and proliferation, by sensing and integrating various signals, such as growth factors, energy status, and amino acids. Our previous studies showed that activation of the mTORC1 signaling pathway enhances silk protein synthesis and silk gland size. Here, the potential of the molecular mechanism mTORC1 to regulate the growth and development of silk gland cells was investigated. Inhibiting mTORC1 with rapamycin decreased proliferation in the Bombyx mori embryonic (BmE) cells and endoreplication in silk gland cells, reducing CyclinB and CyclinE protein levels and DNA content, and arresting the BmE cell cycle at G2/M. Conversely, the overexpression of Ras homolog enriched in brain (Rheb) led to increased proliferation of BmE cells and endoreplication in silk gland cells, as well as a significant elevation in DNA content. This study provides a molecular explanation for the increase in silk protein synthesis and silk gland length through the activation of mTORC1, thereby refining the regulatory network of the silkworm endoreplication and providing new molecular targets for breeding high-yield varieties of Bombyx mori.